Perlindungan Investor Asing Dalam Kegiatan Penanaman Modal Asing Dan Implikasinya Terhadap Negara - Agung Sujati Winata (Universitas Serang Raya, 2018)
Legal protection provided by the state to investors is one of the considerations for foreign investors before investing in a country. This study aims to find out and analyze the legal protection of foreign investment in Indonesian law and implications itself. This research is a descriptive study, which analyzes and describes systematically, factually, and accurately the provisions relating to legal protection against foreign investment in Indonesia. Based on the results of the study, it is known that legal protection against foreign investment in Indonesian law is regulated in the Investment Law. This law has provided adequate protection for foreign investors for a variety of risks including non-commercial risks in foreign investment in Indonesia. Providing the widest opportunity for foreign investors to invest their capital in Indonesia has encouraged many foreign investors to invest in Indonesia.Keywords: Investor, Investment, Legal Protection.